Modification of pharmacokinetic and abuse‐related effects of cocaine by human‐derived cocaine hydrolase in monkeys. (20th January 2012) - Schindler, Charles W.; Justinova, Zuzana; Lafleur, David; Woods, Doug; Roschke, Viktor; Hallak, Hussein; Sklair‐Tavron, Liora; Redhi, Godfrey H.; Yasar, Sevil; Bergman, Jack; Goldberg, Steven R.
ABSTRACT Although substantial research effort has focused on developing pharmacological treatments for cocaine abuse, no effective medications have been developed. Recent studies show that enzymes that metabolize cocaine in the periphery, forestalling its entry into the brain, can prevent cocaine toxicity and its behavioral effects in rodents. Here we report on effects of one such enzyme (Albu‐CocH) on the pharmacokinetic and behavioral effects of cocaine in squirrel monkeys. Albu‐CocH was developed from successive mutations of human butyrylcholinesterase (BChE) and has 1000‐fold greater catalytic activity against cocaine than naturally occurring BChE. Pharmacokinetic studies showed that Albu‐CocH (5 mg/kg) had a half‐life of 56.6 hours in squirrel monkeys. In these studies, plasma levels of cocaine following i.v. 1 mg/kg cocaine were reduced 2 hours after administration of Albu‐CocH, whereas plasma levels of the cocaine metabolite ecgonine methyl ester were increased. These effects were still evident 72 hours following Albu‐CocH administration. In behavioral experiments in monkeys, pre‐treatment with 5 mg/kg Albu‐CocH dramatically decreased self‐administration of a reinforcing dose of i.v. cocaine (30 µg/kg/injection) for over 24 hours. Pre‐treatment with 5 mg/kg Albu‐CocH also attenuated the reinstatement of extinguished cocaine self‐administration by an i.v. priming injection of cocaine (0.1 or 0.3 mg/kg) and, in separate studies, attenuated the discriminative‐stimulus effects of cocaine. The ability of Albu‐CocH to attenuate the abuse‐related effects of cocaine in squirrel monkeys indicates that further investigation of BChE mutants as potential treatment for cocaine abuse and toxicity is warranted.